Pengembangan Aplikasi Mobile Kolepa Berbasis Android Menggunakan Metode Agile - Ilham Firman Ashari; M. Fazar Zuhdi; Muhammad Tyaz Gagaman; Siraz Tri Denira (Politeknik Negeri Batam, 2022)
Kolepa Minigolf and coffe shop is an instance which run on minigolf services also food and beverages. Kolepa wanted to develope a mobile apps that can be use for Kolepa Customer to check on existing promo and book a table to play. Kolepa Mobile Apps will be integrated with Kolepa database. Based on the interview between Project Manager and owner of Kolepa, there's some feature that must be included on the Mobile Apps, which is Authenticate, Promo, Reservation, and Score Counter. In its implementation, agile methods are applied for each of the functions mentioned above. Aplication will be develope using Dart Programming Languange, which is part of Flutter Framework. Application development is divided into several sprints that are developed with predetermined deadlines. From the results of the development that has been carried out, feature testing is carried out using the blackbox method and it is found that the application has met the functional and non-functional requirements that have been set. With this application, Kolepa can simplify the bussiness they run.